(3fRgI GdhLhO aj JMdjI GdCSeGA hGdMOhOs ((3MSfjf TeS s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO agPg MOhO Jdjb HWGdH GdYde GdTQa GYde Cf GddaX ai GddZI YHGQI Yf GdQei hai GdGUWdGM YHGQI YeG jJdaX Hg GdEfSGf s
(3BNQgG (B:s
(3GdGSe daX jOd Ydi eYfi ai faSg ZjQ ebJQf HReGf s
(3GdeNWhW eeG LeYg YQH TGg hZjQgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda SfI (B1303s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs